Calcium, Magnesium and Phosphorous Levels in Serum of Iraqi Women with Fibromyalgia - Ali A. Kasim (College of Pharmacy University of Baghdad, 2017)
Fibromyalgia (FM) is a common, debilitating, and chronic pain syndrome. The women are more likely to have more tender points on examination than are their male counterparts. Iraqi study showed that FM occur in 1.5% among adolescents of Iraqi population. In compare to normal healthy women, present study was revealed that Iraqi women with FM have significant elevation of calcium (p = 0.003) with significant reduction of magnesium (p = 0.001), whereas the inorganic phosphorous was not differs (p = 0.31). In conclusion, magnesium and calcium would play a crucial role in etiopathogenesis of fibromyalgia. Key words: calcium, magnesium, phosphorous, Fibromyalgia.